Ferromagnetism and superconductivity in CeFeAs 1-xP xO (0≤x≤40) - Jesche, A.; Förster, T.; Spehling, J.; Nicklas, M.; De Souza, M. [UNESP]; Gumeniuk, R.; Luetkens, H.; Goltz, T.; Krellner, C.; Lang, M.; Sichelschmidt, J.; Klauss, H. H.; et al. (American Physical Society (APS), 2012)
We report on superconductivity in CeFeAs 1-xP xO and the possible coexistence with Ce ferromagnetism (FM) in a small homogeneity range around x=30% with ordering temperatures of T SC≅T C≅4 K. The antiferromagnetic (AFM) ordering temperature of Fe at this critical concentration is suppressed to TNFe≈40 K and does not shift to lower temperatures with a further increase of the P concentration. Therefore, a quantum-critical-point scenario with TNFe→0 K which is widely discussed for the iron based superconductors can be excluded for this alloy series. Surprisingly, thermal expansion and x-ray powder diffraction indicate the absence of an orthorhombic distortion despite clear evidence for short-range AFM Fe ordering from muon-spin-rotation measurements. Furthermore, we discovered the formation of a sharp electron spin resonance signal unambiguously connected with the emergence of FM ordering. © 2012 American Physical Society.